2013
DOI: 10.1302/0301-620x.95b7.31174
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged incubation time does not increase sensitivity for the diagnosis of implant-related infection using samples prepared by sonication of the implants

Abstract: We have designed a prospective study to evaluate the usefulness of prolonged incubation of cultures from sonicated orthopaedic implants. During the study period 124 implants from 113 patients were processed (22 osteosynthetic implants, 46 hip prostheses, 54 knee prostheses, and two shoulder prostheses). Of these, 70 patients had clinical infection; 32 had received antibiotics at least seven days before removal of the implant. A total of 54 patients had sonicated samples that produced positive cultures (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Butler-Wu et al suggested that for all periprosthetic specimens, minimal aerobic and anaerobic culture incubation periods of 13 days are highly recommended (29). However, Esteban et al and Schwotzer et al reported that compared with a 7-day incubation period, a 14-day incubation period does not add more positive results for sonicated orthopedic implants (28,33). In this meta-analysis, six studies were cultured anaerobically for 7 days and five studies were cultured anaerobically for 14 days.…”
mentioning
confidence: 90%
“…Butler-Wu et al suggested that for all periprosthetic specimens, minimal aerobic and anaerobic culture incubation periods of 13 days are highly recommended (29). However, Esteban et al and Schwotzer et al reported that compared with a 7-day incubation period, a 14-day incubation period does not add more positive results for sonicated orthopedic implants (28,33). In this meta-analysis, six studies were cultured anaerobically for 7 days and five studies were cultured anaerobically for 14 days.…”
mentioning
confidence: 90%
“…A recent study states that the use of prolonged incubation times for solid media failed to increase the detection of implant-related infections [5]. Therefore for 250 patients we extended incubation of AC plates.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the majority of bacterial cultures of tissues and fluids obtained from sterile sites are incubated for 5 days or less [5,6]. Antimicrobial therapy before sampling, slow and fastidious growth of microorganisms and changes in metabolism due to growth in biofilm are among the reasons for a high rate of false negative results of culture [3].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the infection is eradicated but it is not possible to retain good joint function, in which case arthrodesis or amputation may be the end result, which is considered as salvage procedure. 6,10,12,18,[23][24][25][26][27][28][29][30][31][32][33] The choice of the best treatment is based on several factors including the characteristics of the patient, the type of germ involved, the duration of symptoms and the condition of bone and soft tissues. Recently Tsukayama et al 34 have proposed a clinical classification with the aim to help the surgeon to make a choice of the appropriate management.…”
Section: Treatment Optionsmentioning
confidence: 99%